Mycobacterium neoaurum Bloodstream Infection Associated with a Totally Implanted Subclavian Port in an Adult with Diabetes and History of Colon Cancer - Jack E. Moseley Jr.; Sharanjeet K. Thind (Case Reports in Infectious Diseases)
Background. Mycobacterium neoaurum is a rapidly growing nontuberculosis mycobacterium (NTM) that was first isolated from soil in 1972 and is ubiquitous in soil, water, and dust. The first reported case of human infection by M. neoaurum was published in 1988, presenting as a Hickman catheter-related bacteremia in a patient with ovarian cancer. M. neoaurum has since been recognized as a source of predominantly opportunistic bloodstream infections in immunocompromised hosts. We report the case of an adult diabetic male with M. neoaurum bloodstream infection secondary to an infected venous-access port that had been implanted nearly six years prior for temporary chemotherapy. Case Presentation. A 66-year-old male with schizophrenia, type 2 diabetes mellitus, and a history of excision and chemotherapy to treat adenocarcinoma of the colon 6 years prior, presented with fever and behavioral changes. He was found to have a M. neoaurum bloodstream infection secondary to his implanted subclavian port. Multiple preoperative blood cultures, as well as the removed catheter tip culture, were positive for M. neoaurum. The patient’s condition improved to near premorbid levels after port removal and 6 weeks of targeted antimicrobial therapy. Discussion and Conclusions. Bloodstream infections due to rapidly growing NTM, such as M. neoaurum, have been infrequently reported; however, improved isolation and identification techniques based on genomic testing are resulting in a more in-depth recognition of these widely scattered environmental microbes in human infections. Nonetheless, lengthy identification and susceptibility processes remain a diagnostic and treatment barrier. Patients such as ours who have a history of malignancy and an indwelling foreign body have most often been reported as acquiring M. neoaurum bacteremia. Fortunately, device removal and appropriate antimicrobial therapy guided by susceptibility data is often enough to manage these atypical mycobacterial infections.